Does the Use of Injectable Atelocollagen during Arthroscopic Rotator Cuff Repair Improve Clinical and Structural Outcomes? - In Bo Kim; Eun Yeol Kim; Kuk Pil Lim; Ki Seong Heo (Clinics in Shoulder and Elbow, 2019)
Background Since the establishment of biological augmentation to improve the treatment of rotator cuff tears, it is imperative to explore newer techniques to reduce the retear rate and improve long-term shoulder function after rotator cuff repair. This study was undertaken to determine the consequences of a gel-type atelocollagen injection during arthroscopic rotator cuff repair on clinical outcomes, and evaluate its effect on structural integrity. Methods Between January 2014 and June 2015, 121 patients with full thickness rotator cuff tears underwent arthroscopic rotator cuff repair. Of these, 61 patients were subjected to arthroscopic rotator cuff repair in combination with an atelocollagen injection (group I), and 60 patients underwent arthroscopic rotator cuff repair alone (group II). The visual analogue scale (VAS) for pain and the Korean Shoulder Society (KSS) scores were evaluated preoperatively and postoperatively. Magnetic resonance imaging (MRI) was performed at 6 months postoperatively, to assess the integrity of the repair. Results VAS scores were significantly lower in group I than in group II at 3, 7, and 14 days after surgery. KSS scores showed no significant difference between groups in the 24 months period of follow-up. No significant difference was obtained in the healing rate of the rotator cuff tear at 6 months postoperatively (p=0.529). Conclusions Although a gel-type atelocollagen injection results in reduced pain in patients at 2 weeks after surgery, our study does not substantiate the administration of atelocollagen during rotator cuff repair to improve the clinical outcomes and healing of the rotator cuff.